Research and test of the measurement sensing device for the downforce of no-till planter row unit gauge wheels - Shang, Jiajie; Liu, Liyi; Zhang, Ruifeng; Li, Hongcheng; Hou, Shouyin; Liu, Hongxin; Chen, Haitao (International Journal of Agricultural and Biological Engineering, 2024)
To effectively obtain the downforce of the gauge wheels in real time, mechanical models of the interaction among the ground, gauge wheels, gauge wheel arms, and depth adjustment lever were constructed. A measuring method was proposed for monitoring the downforce through a two-dimensional radial sensing device, and a corresponding prototype was designed. Through simulation analysis of the sensing device with ANSYS, a 45° angle was determined to exist between the strain gauge axis and the sensing device axis, and the Wheatstone bridging circuit of R1+R3−R5−R7 (R stands for resistance strain gauge, different figures represent the strain gauge number) and R2+R4−R6−R8 was adopted. According to performance and calibration tests for the sensing device, the maximum interaction effect between the X and Y axes was 2.52%, and the output signal was stable and consistent. The standard error of the slope of the fitting equation of the downforce calculation model is 0.008. According to the field test, the average downforce of the gauge wheels was 1148, 1017, 843, and 713 N, at different sowing speeds of 6, 8, 10, and 12 km/h, respectively. The coefficients of variation were 0.40, 0.41, 0.62, and 0.71, respectively. The results indicate that the downforce fluctuation of the gauge wheels became more severe with increasing planting speed. Both the strain simulation analysis and field test verified that the measurement method is accurate and reliable, the performance of the sensing device is stable, the measurement method and sensing device meet the application requirements and lay a foundation for the research of accurate and stable control of downforce of no-till planter. Key words: no-till planter; gauge wheel downforce; two-dimensional radial force sensing device; strain analysis; measurement mode and method DOI: 10.25165/j.ijabe.20241703.8484 Citation: Shang J J, Liu L Y, Zhang R F, Li H C, Hou S Y, Liu H X, et al. Research and test of the measurement sensing device for the downforce of no-till planter row unit gauge wheels. Int J Agric & Biol Eng, 2024; 17(2): 250–259.